The Influence of Financial Literacy, Financial Inclusion, and Financial Technology on the Financial Performance of MSMEs with Financial Management Behavior as a Mediating Variable (Study on MSMEs in the Agriculture, Culinary, and Tourism Sectors in Subang Regency, West Java) - Titin Kartini; Keni Kaniawati; Fatimah Nurjannati Iskandar (Journal of Economics and Management Scienties, 2026)
This study examines the influence of financial literacy, financial inclusion, and financial technology (fintech) on the financial performance of MSMEs, with financial management behavior as the mediating variable. The study was conducted on MSMEs in the agricultural, culinary, and tourism sectors in Subang Regency, West Java. Adopting a quantitative explanatory approach, this study collected data from 250 purposively sampled respondents and analyzed it using SmartPLS 4's PLS-SEM. The results indicate that financial management behavior is significantly shaped by financial literacy (β = 0.513; p = 0.006) and, even more strongly, by financial inclusion (β = 0.681; p < 0.001), while financial technology shows no significant direct effect. Neither variable directly affects MSME financial performance in a practically meaningful way; however, financial management behavior is the dominant predictor of financial performance (β = 0.726; p < 0.001; R² = 0.614). Financial management behavior plays a significant mediating role in how financial literacy influences financial performance (0.481; p = 0.006) and the effect of financial inclusion on financial performance (0.549; p < 0.001), but not the effect of financial technology. These findings confirm that financial management behavior is the critical bridge between financial resources knowledge and access and actual business performance, supporting a knowledge behavior performance chain model for rural MSMEs in Indonesia.